Dynamic adaptive pathways planning for adaptation: lessons learned from a decade of practice in Aotearoa New Zealand - Judy Lawrence; Shari L. Gallop; Lisa Marquardt; Rob Bell; Paula Blackett; Nicholas A. Cradock-Henry; Anita Wreford (Journal of Integrative Environmental Sciences)
There is a climate change adaptation implementation gap. We have information about the likely impacts and implications, but concrete pre-emptive action is elusive. Key to addressing this are alternative planning approaches that enable decision makers to anticipate impacts and design alternate pathways depending on how conditions change, in time for adaptation actions to be implemented. Over the last ten years, dynamic adaptive pathways planning (DAPP) has been applied in Aotearoa New Zealand (A-NZ) to assist in such circumstances. Pathways planning has now been applied in diverse decision settings and has motivated the use and development of complementary methods and tools for evaluating adaptation options and pathways. Different governance and engagement models have emerged, tailored with and for different communities. DAPP research and practice in A-NZ has advanced the design of monitoring systems, decision signals and triggers, staging managed retreat over time, and serious games to prime decision makers for dealing with uncertainty. Māori (the Indigenous people of A-NZ) worldviews, knowledge and values have intersected and informed DAPP applications, but significant untapped opportunities exist. This paper presents lessons learned from these applications and further research needed. Opportunities for supporting and extending the DAPP process for adaptation decision making through governance, engagement and indigenous knowledge and values are suggested.